The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/ncomms15508
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 induced NOTCH1 activation in oligodendrocyte progenitor cells enhances proliferation and inflammatory gene expression

Abstract: NOTCH1 signalling contributes to defective remyelination by impairing differentiation of oligodendrocyte progenitor cells (OPCs). Here we report that IL-17 stimulation induces NOTCH1 activation in OPCs, contributing to Th17-mediated demyelinating disease. Mechanistically, IL-17R interacts with NOTCH1 via the extracellular domain, which facilitates the cleavage of NOTHC1 intracellular domain (NICD1). IL-17-induced NOTCH1 activation results in the interaction of IL-17R adaptor Act1 with NICD1, followed by the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 44 publications
2
91
0
Order By: Relevance
“…In particular, cytokine exposure during the proliferative phase leads to an increased proliferation and a differentiation block in both fetal and adult OPCs, as indicated by lineage progression marker analysis. Numerous in vitro and in vivo studies have indicated that inflammatory cytokines promote OPC proliferation, involving, among others, the VEGFR2 (Choi et al, 2018) and Notch pathways (Wang et al, 2017). Inflammatory cytokines are also proved to be involved specifically in the differentiation block of OPCs derived from the adult brain, affecting cell cycle exit and the expression of genes encoding for proteins that regulate and determine remyelination (Chew, King, Kennedy, & Gallo, 2005;Falahati et al, 2013;Kang et al, 2013;Su et al, 2011;Tanner, Cherry, & Mayer-Pröschel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cytokine exposure during the proliferative phase leads to an increased proliferation and a differentiation block in both fetal and adult OPCs, as indicated by lineage progression marker analysis. Numerous in vitro and in vivo studies have indicated that inflammatory cytokines promote OPC proliferation, involving, among others, the VEGFR2 (Choi et al, 2018) and Notch pathways (Wang et al, 2017). Inflammatory cytokines are also proved to be involved specifically in the differentiation block of OPCs derived from the adult brain, affecting cell cycle exit and the expression of genes encoding for proteins that regulate and determine remyelination (Chew, King, Kennedy, & Gallo, 2005;Falahati et al, 2013;Kang et al, 2013;Su et al, 2011;Tanner, Cherry, & Mayer-Pröschel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…IL‐17A, secreted by immune cells, plays a vital role in the stroke pathophysiology. In addition to its pro‐inflammatory effect, IL‐17A has been shown to promote hyperproliferation and differentiation of various cell types; the most notable are Th17 cells and γδT cells due to their production of IL‐17A . After hemorrhagic stroke, macrophages become activated and secret IL‐23, which promotes the activation of γδT cells and Th cells .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its pro-inflammatory effect, IL-17A has been shown to promote hyperproliferation and differentiation of various cell types; the most notable are Th17 cells and γδT cells due to their production of IL-17A. 17,[45][46][47][48] After hemorrhagic stroke, macrophages become activated and secret IL-23, which promotes the activation of γδT cells and Th cells. 18 Due to the blood-brain barrier (BBB) rupture after hemorrhagic stroke, 49 IL-17A enters into the brain tissue through the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Notch1 receptor has been shown to modulate T cell chemotaxis to the CNS, T cell IFN-γ and IL-17 expression in Th1 and Th17 cells, and Treg functions [37]. Finally, a role for Notch1 in the IL-17 promotion of oligodendrocyte proliferation and inhibition of differentiation has also been described in relation to EAE progression [44].…”
Section: Discussionmentioning
confidence: 99%